PROMOTIONAL VIDEO DESIGN ABOUT TOURISM INFORMATION IN KARIMUN - Mangapul Siahaan; Oktavina Oktavina (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
In this era of modernization, social media has become a popular platform means of communication and is the choice of the community, social media is also growing rapidly from various classifications and types according to needs. Promotional videos made on YouTube social media are now widely used by companies and governments to promote their products or introduce tourist attractions. The tourism sector has an important and profitable role and has the potential to be developed as an asset that is a source of income for the nation and state. So that video promotion media is considered to be able to fulfil the needs of the wider community in presenting information and conducting promotions that are more interesting and interactive. In making a promotional video that aims to introduce tourist attractions on Karimun Island, the author uses the Media Production Concept (KPM) method which consists of Pre Production, Production, Post Production to assist the video design process and data collection by means of documentation and interviews with visitors and the author uses Adobe Premiere Pro 2020 software in video editing. The results of this study are in the form of a video that summarizes tourist attractions on Karimun Island in the hope of attracting local and foreign people to visit Karimun Island